Assessing the surface roughness of a posterior resin composite: effect of surface sealing - Takeuchi, CYG; Flores, VHO; Dibb, RGP; Panzeri, H.; Lara, EHG; Dinelli, W. (Operative Dentistry Inc, 2003)
This study assessed the in vitro influence of surface sealing on the surface roughness of a posterior resin composite before and after tooth-brushing. Thirty. specimens (13 nun diameter x 1 mm high) were fabricated from Filtek-P60 resin composite and randomly assigned to three groups (n=10): a non-sealed control and two groups sealed with one of the tested materials-a surface-penetrating sealant (Protect-it!-PI) and a one bottle adhesive system (Single Bond-SB). The samples were subjected to a surface roughness reading to determine the initial roughness, then submitted to simulated toothbrushing with 35,600 cycles for 100 minutes. Specimens were then cleaned and a post-abrasion surface roughness reading accomplished. Means (pm), recorded before (B) and after (A) toothbrushing, and standard deviations were: Control-(B): 0.032 (+/-0.005), (A): 0.054 (+/-0.005); PI-(B): 0.034 (+/-0.005), (A): 0.060 (+/-0.034); SB (B): 0.031 (+/-0.004), (A): 0.047 (+/-0.007). Data were tabulated and submitted to two-way ANOVA. No statistically significant difference was observed when the control and experimental groups were compared. However, a significant difference (p<0.05) was found between the measurements performed before and after toothbrushing. Based on these results, it may be concluded that using either a surface penetrating sealant or a one bottle adhesive system did not provide the optimization of superficial integrity. The use of a dentifrice and toothbrush resulted in significant alterations to the surface smoothness of the resin composite.